Proceedings of the 20th ACM International Conference on Intelligent Virtual Agents 2020
DOI: 10.1145/3383652.3423888
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Virtual Agent's Non-Verbal Emotional Expression on a User's Personal Space Preferences

Abstract: Virtual-reality-based interactions with virtual agents (VAs) are likely subject to similar influences as human-human interactions. In either real or virtual social interactions, interactants try to maintain their personal space (PS), an ubiquitous, situative, flexible safety zone. Building upon larger PS preferences to humans and VAs with angry facial expressions, we extend the investigations to whole-body emotional expressions. In two immersive settingsśHMD and CAVEś66 males were approached by an either happy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, researchers have implemented behaviors to maintain certain distances between users depending on the situation to achieve acceptable conversational interaction in virtual environments [ 14 , 15 ]. Similar to physical environments, people’s personal space preferences are influenced by several factors, e.g., the agents’ emotional expressions [ 16 ] and touching behaviors [ 17 , 18 ]. These studies suggested that addressing such knowledge is critical for designing acceptable virtual agents in a virtual environment.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, researchers have implemented behaviors to maintain certain distances between users depending on the situation to achieve acceptable conversational interaction in virtual environments [ 14 , 15 ]. Similar to physical environments, people’s personal space preferences are influenced by several factors, e.g., the agents’ emotional expressions [ 16 ] and touching behaviors [ 17 , 18 ]. These studies suggested that addressing such knowledge is critical for designing acceptable virtual agents in a virtual environment.…”
Section: Related Workmentioning
confidence: 99%
“…The notion behind it is that people will keep similar distances to virtual characters in VR as they do with real people when social presence is sufficiently high. For example, similar distance patterns which exist in real life were discovered in VR when assessing, e.g., the effect of age and gender (Iachini et al, 2016 ), attractiveness (Zibrek et al, 2020 ), and facial expression (Bönsch et al, 2020 ). Other indirect measures include eye-tracking and psychophysiological measurements (Slater et al, 2009 ).…”
Section: The Problem Of Indirect Measures Of Social Presencementioning
confidence: 70%
“…The existence of personal space has been confirmed in VE, and the same trend as in many REs has been observed [12], [60]- [64]. In addition, it is easier to control the conditions and to measure the participants in experiments in VE than in RE, which makes it easier to conduct research with an increased number of interpersonal people [65] and to measure the anxiety felt [43], [66].…”
Section: B Interpersonal Distance Researchmentioning
confidence: 85%
“…One's impression of others can be manipulated by changing the elements of the avatar in VE. Reference [12] showed that interpersonal distance changes with differences in avatars' facial expressions, and Ref. [13] emphasized that interpersonal distance changes with differences in an avatar's eye movements.…”
Section: B Objectives and Contributionsmentioning
confidence: 99%